A Challenging Case of Kikuchi-Fujimoto Disease Associated with Systemic Lupus Erythematosus and Review of the Literature. (23rd January 2018) - Găman, Mihaela; Vlădăreanu, Ana-Maria; Dobrea, Camelia; Onisâi, Minodora; Marinescu, Cristina; Voican, Irina; Vasile, Daniela; Bumbea, Horia; Cîşleanu, Diana
Abstract : Kikuchi–Fujimoto disease (KFD) or histiocytic necrotizing lymphadenitis is a rare disease that is frequently underdiagnosed due to clinical features that are similar to those of non-Hodgkin lymphomas, systemic lupus erythematosus (SLE), or infectious reactive lymphadenopathy. An excisional biopsy is required. We report a young Caucasian female diagnosed with KFD with skin lesions, complicating with SLE. The clinical course, laboratory, and CT findings are described, as are histopathologic features, for a better recognition of this rare disorder in clinical practice.